Model Berbasis Fuzzy Tsukamoto Untuk Perhitungan Besaran Gaji Dosen Pada Perguruan Tinggi Swasta - Valian Yoga Pudya Ardhana; Eliyah A. M. Sampetoding; Danang Tejo Kumoro; Noor Alamsyah (Universitas Budi Darma, 2022)
Payment of salaries is a routine activity carried out by the finance department of a company, agency or business entity. Likewise, private universities which are educational institutions have an obligation to pay the salaries of their lecturers. With the large number of lecturers and the many variables in determining the amount of lecturer salaries, it is difficult for the finance department at private universities to determine the amount of a fair salary and in other words provide a salary that is in accordance with the efforts that have been made by each lecturer. With these problems, we need a method of calculating teacher salaries. The fuzzy tsukamoto method is the most ideal method in determining the salary of lecturers at private universities because it has non-binary and non-linear problems. With the problems and solutions raised above, this study aims to provide a faster, more precise and accurate method of calculating lecturer salaries at private universities, of course with input variables that are adjusted to the rules in private universities. Salary variables, especially lecturer salary bonuses at private universities, are years of service, jafung, rank/class and the most important is the performance variable. In the performance variable, there are three specific variables, namely the tridharma of lecturers (teaching, research or publication, and community service). To achieve a bonus with many criteria, it is required that the three performance variables have many criteria, and vice versa.